A Software Framework to Create 3D Browser-Based Speech Enabled Applications - Pizzolato, Ednaldo Brigante; Duarte, Diego Daniel; Fernandes, Marcio Merino (Revista de Informática Teórica e Aplicada, 2009)
The advances in automatic speech recognition have pushed the humancomputer interface researchers to adopt speech as one mean of input data. It is natural to humans, and complements very well other input interfaces. However, integrating an automatic speech recognizer into a complex system (such as a 3D visualization system or a Virtual Reality system) can be a difficult and time consuming task. In this paper we present our approach to the problem, a software framework requiring minimum additional coding from the application developer. The framework combines voice commands with existing interaction code, automating the task of creating a new speech grammar (to be used by the recognizer). A new listener component for the Xj3D was created, which makes transparent to the user the integration between the 3D browser and the recognizer. We believe this is a desirable feature for virtual reality system developers, and also to be used as a rapid prototyping tool when experimenting with speech technology.